Anticancer and Anti-metastatic Effects of Supercritical Extracts of Hops (Humulus lupulus L.) and Mango ginger (Curcuma amada Roxb.) in Human Glioblastoma - Cheppail Ramachandran; Ashley Juan; Karl-W. Quirin; Laila Khatib; Enrique Escalon; Ziad Khatib; Steven J. Melnick (International Journal of Phytomedicine, 2018)
Glioblastoma is one of the most aggressive, lethal and incurable primary brain tumors with a dismal prognosis in humans. Mango ginger (Curcuma amada) and hops (Humulus lupulus) are two botanicals containing phytochemicals with potential anticancer effects. We have investigated the anticancer and antimetastatic properties of supercritical CO2 extract of mango ginger (CA) and ethanol extract of hops (HL) in the U-87MG human glioblastoma cell line. Both CA and HL individually demonstrate strong cytotoxicity against glioblastoma cells. CompuSyn analysis of cytotoxicity data confirms that CA and HL are synergistic for cytotoxicity with combination index (CI) values of <1.0. Additionally, CA and HL individually as well as the combination significantly inhibit MMP-2 and MMP-9 activity, tumor cell migration (transendothelial cell migration assay) and AKT phosphorylation in U-87MG cells. CA and HL inhibit glycolysis in U-87MG cells as indicated by the inhibition of ATP and lactate synthesis with the CA+HL combination demonstrating strong inhibition of glycolysis via the reduction of ATP and lactate synthesis compared to cells treated by each extract alone. CA and HL treatment down regulates the expression of proteins associated with metastasis, MMP-2 and MMP-9 and up regulates the expression of TIMP1. Proteins associated with apoptosis, inflammation and energy metabolism were also modulated by CA and HL treatment of glioblastoma cells. These results suggest that CA and HL can be combined for the therapeutic management of glioblastomas.